Comparison of risk factors, management and outcome between early and lately detected gestational diabetes mellitus patients - Mohammad Moin Shahid; Richmond Ronald Gomes; KM Thouhidur Rahman; ABM Kamrul Hasan; Shah Mohammad Fahim (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Aim: The aim of this study is to compare the risk factors, management and pregnancy outcome between the Gestational Diabetes Mellitus (GDM) patients who were diagnosed at early and late stage of pregnancy.  Methods: We randomly selected 250 newly detected GDM patients and examined them. They were divided into two groups considering the gestational age at the time of diagnosis: early group (13 to 28 weeks) and late group (after 28 weeks).  Results: Data of 150 cases from early group and 100 cases from late group were analyzed. Incidence of nulliparous GDM patient (24% vs 36%, P - 0.04),weight at the time of GDM diagnosis (66.0 ± 11.067 vs 69.93 ± 9.865, P - 0.004) were significantly higher in late group and so was the excess body weight from ideal body weight (14.13 ± 10.147 vs 17.94 ± 8.535, P - 0.002). Prevalence of pre pregnancy obese/ overweight patients (68.7% vs 80.0%, P - 0.047), maternal H/O of DM (45.3% vs 32%, p - 0.035) and H/O unexplained fetal loss (24% vs 10%, p - 0.005) were higher in early group. There were no significant differences of blood sugar values (SMBG) between the groups except fasting blood sugar at 2nd visit (F2) (5.557 ± 1.045 vs 5.167 ± 0.960, P - 0.01).  Conclusion: This study suggests that range of screening should be broader to detect high risk and undiagnosed GDM mothers. Beside that it has also showed that only early diagnosis and intervention will not be enough to prevent the complications if the patients fails to understand and participate in GDM management.